2017
DOI: 10.1007/s00449-017-1785-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of para-hydroxybenzoic acid by genetically engineered Saccharomyces cerevisiae

Abstract: Saccharomyces cerevisiae is a popular organism for metabolic engineering; however, studies aiming at over-production of bio-replacement precursors for the chemical industry often fail to overcome proof-of-concept stage. When intending to show real industrial attractiveness, the challenge is twofold: formation of the target compound must be increased, while minimizing the formation of side and by-products to maximize titer, rate and yield. To tackle these, the metabolism of the organism, as well as the paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Further, ubiC was screened against the mutated version ubiC CCSS , which supposedly has enhanced solubility (Holden et al, 2002 ). Surprisingly ubiC still performed better (Averesch et al, 2017 ), also kinetic limitations appeared to be not as profound as reported (Holden et al, 2002 ). The strain was then used to stepwise develop a production process; in a fed-batch bioreactor a final titer of 2.9 g/L could be reached, at a productivity of almost 30 mg/(L × h) and a yield that reached 4% of the theoretical maximum.…”
Section: Results—strain Engineering Strategies For Production Of Arommentioning
confidence: 70%
“…Further, ubiC was screened against the mutated version ubiC CCSS , which supposedly has enhanced solubility (Holden et al, 2002 ). Surprisingly ubiC still performed better (Averesch et al, 2017 ), also kinetic limitations appeared to be not as profound as reported (Holden et al, 2002 ). The strain was then used to stepwise develop a production process; in a fed-batch bioreactor a final titer of 2.9 g/L could be reached, at a productivity of almost 30 mg/(L × h) and a yield that reached 4% of the theoretical maximum.…”
Section: Results—strain Engineering Strategies For Production Of Arommentioning
confidence: 70%
“…3 These prices indicate the dutiable value on the US border prior to applying tariffs and in our opinion reflect the bulk prices for chemicals robustly. We assume that a mineral medium is based on a previously published yeast-based process (Averesch et al, 2017). For the bacterial process, it is assumed that sucrose metabolism is as active as glucose metabolism, which was previously demonstrated for certain strains of Escherichia coli (Arifin et al, 2014), for instance.…”
Section: Substratesmentioning
confidence: 99%
“…For this simulation we assume a production either with a recombinant strain of baker's yeast as described previously (Averesch et al, 2017) or an optimized strain of Corynebacterium glutamicum (Kitade et al, 2018). The yeast-based process could be run in an acidic pH range and potentially under anaerobic conditions, while the bacterial process needs to be controlled around pH 7.0 with sufficient aeration.…”
Section: Biocatalystsmentioning
confidence: 99%
“…To increase the flux to chorismate, they expressed ARO4 K229L and aroL. This strain was then used and allowed a PHBA formation from CHO, with a titer of 2.9 g L −1 and yield of 3.1 mg g glucose −1 , in a fed-batch process (Averesch et al, 2017). To date, the highest PHBA titer was reported by Kitade et al (2018) in C. glutamicum (Table 1).…”
Section: Strategies For Production Of Aromatic Compoundsmentioning
confidence: 99%